Evaluation of response to hepatitis B vaccine in Iranian 6–18-year-old students - Jouneghani, Alizamen Salehifard (J Res Med Sci, 2017)
BACKGROUND: Hepatitis B is a dangerous disease with high morbidity and mortality rates all around the world. Vaccination is the most important way to its prevention and control. This cross-sectional study was carried out to study the levels of immunogenicity to hepatitis B vaccine in students. MATERIALS AND METHODS: Six hundred and forty-four students aged 6–18 years including 316 girls and 328 boys were selected from the Chaharmahal Va Bakhtiari province. Selected students had been received three doses of recombinant vaccine (0, 1, and 6 months). Blood samples were taken and the titers of hepatitis B surface antigen were studied. RESULTS: From a total of 644 students, 396 (61.5%) had a titer lesser than 10 mIu/ml and 248 (38.5%) had a titer higher than 10 mIu/ml. Therefore, the level of respond to vaccine with 95% confidence was 38.5% (34.7%–42.4%). Levels of respond to vaccine were related to age, body mass index (BMI), and educational level and were not related to sex and habit of students. CONCLUSION: Reverse significant relation was seen between the respond to vaccine and age and BMI in a way which the titers of antibody were lower in students with higher age and BMI.